Normative Dualism In The Indonesian Legal System: The Dynamics of The Relationship Between Sharia And Positive Law - Terry Rongga Nugraha; Mutiara Apriliyani; Afendi Yosuf (Socio Legal and Islamic Law, 2025)
This article examines the normative dualism arising from the coexistence of Islamic law and positive law within the Indonesian legal system. As a pluralistic legal state, Indonesia accommodates both religious norms and statutory regulations, creating challenges in achieving legal certainty and consistency. This study employs a normative juridical method through statutory and conceptual approaches to analyze the interaction between sharia principles and positive law. The findings indicate that normative dualism often leads to interpretative inconsistencies and institutional fragmentation, while simultaneously reflecting Indonesia’s commitment to legal pluralism. The study argues that legal harmonization through integrative interpretation and regulatory accommodation is necessary to bridge the gap between religious and state legal norms. Such harmonization is essential to strengthen legal certainty, preserve constitutional values, and support the development of a coherent national legal system